The effect of Learning Styles to Build Learner Autonomy - Ratna Sajekti Rusli; Helena D.; Soegiarto Soegiarto (TEFLIN, 2001)
The purpose of this study was to investigate the effect of field-dependent and field-independent cognitive learning styles on learning achievement and the relation between cognitive learning and gender. The subjects were SMU students of Social Science (IPS) and Mathematics and Natural Science (IPA) classes of SMUK Triyana. The scores of summative test od several school subject matters were used as the data. The results show that cognitive learning styles do not have any effect on the students acievement on History subject matter. However, cognitive learning styles influence English learning. This study also shows that gender does not affect achievement.